Perfil epidemiológico dos óbitos por neoplasia colorretal no estado de Alagoas dos anos de 2018 a 2022. - Ana Carolina Maia Araújo (2024)
Colorectal cancer (CRC) is a malignant neoplasm characterized by affecting the large intestine and rectum, being the third most common neoplasm in Brazil, which represents a public health problem. The most prevalent signs and symptoms are changes in intestinal transit and weight loss, followed by abdominal pain, hematochezia and anemia. Several risk factors for CRC are indicated in studies, making it necessary to change lifestyle to reduce the incidence of mortality in people with the disease. To this end, there is a wide variety of options available for the treatment of colorectal cancer depending on the stage. The data for analysis were obtained from the Mortality Information System (SIM) of the Department of Informatics of the Unified Health System (DATASUS). To ensure data integrity, incomplete records or those that presented inconsistencies were excluded. Mortality rates may vary between different regions of the state, education level, age group and gender. Therefore, tracking and early detection are essential to reduce mortality. For this reason, the present study aims to carry out an analysis of the epidemiological profile of deaths due to colorectal neoplasia in the state of Alagoas from 2018 to 2022. Keywords:  Colorectal cancer, Public health, Mortality.